The Interlocutory Mareva Injunction to Freeze the Assets and Property of the debtor in the English Law: A Comparative Analytical study with the precautionary seizure in the Iraqi Law - Younis salahuddin Ali (Journal of Legal Sciences, 2024)
The interim protective order to freeze the assets or property of the debtor, for the interest of his or her creditors, known as the Mareva injunction is considered as one of the most considerable means of the precautionary and conservative seizure, and interlocutory remedies available to the creditor, which is included in the English Common law of customary origins, which is unwritten and based upon judicial precedents of the English courts. It is worth-bearing in mind that although the origin and the development of this legal system date back to the principles of equity, but it became as a part of the English common law. Before being codified by the English parliament, and given legislative features or characteristics, and included within, and provided for in the High court Act 1981. Therefore, it is regarded nowadays as a precautionary measure providing an interlocutory relief, and a judicial and emergent remedy for the creditor, containing the freeze of his or her assets or property of the debtor, to prevent him or her from removing or dissipating them. In return the Iraqi law of civil proceedings No. (83) of 1969  regulated a similar protective and conservative means, represented by the precautionary seizure, aimed also at keeping the assets or property of the debtor, and conserving them.